A rare case of testicular dislocation with inguinal hernia as a delayed presentation after scrotal trauma - Kumar, Sanjana; Arora, Jainendra K.; Kumar, Ajay (International Surgery Journal, 2020)
Testis can be damaged either by blunt or penetrating trauma. Traumatic dislocation of testis is rare sequelae of scrotal trauma. Patients usually present at the time of injury and diagnosis is usually made on emergent basis. However, delayed or missed diagnosis may occur as scrotal injury may be overlooked in the presence of other associated injuries or due to lack of awareness of its possible occurrence. In this article, we report a case of 60 years old gentleman who presented with inguinal hernia with empty left hemiscrotum with history of blunt injury to scrotum 15 years back. The peculiarity of case lies in the fact that the dislocation of testis was diagnosed 15 years after trauma and the displaced testis was found to be atrophic.